Our current understanding of the biological impact of endometrial cancer mtDNA genome mutations and their potential use as a biomarker - Khadka, Pabitra; Young, Carolyn K. J.; Sachidanandam, Ravi; Brard, Laurent; Young, Matthew J. (Frontiers in Oncology, 2024)
Endometrial cancer (EC) is a devastating and common disease affecting women's health. The NCI Surveillance, Epidemiology, and End Results Program predicted that there would be >66,000 new cases in the United States and >13,000 deaths from EC in 2023, and EC is the sixth most common cancer among women worldwide. Regulation of mitochondrial metabolism plays a role in tumorigenesis. In proliferating cancer cells, mitochondria provide the necessary building blocks for biosynthesis of amino acids, lipids, nucleotides, and glucose. One mechanism causing altered mitochondrial activity is mitochondrial DNA (mtDNA) mutation. The polyploid human mtDNA genome is a circular double-stranded molecule essential to vertebrate life that harbors genes critical for oxidative phosphorylation plus mitochondrial-derived peptide genes. Cancer cells display aerobic glycolysis, known as the Warburg effect, which arises from the needs of fast-dividing cells and is characterized by increased glucose uptake and conversion of glucose to lactate. Solid tumors often contain at least one mtDNA substitution. Furthermore, it is common for cancer cells to harbor mixtures of wild-type and mutant mtDNA genotypes, known as heteroplasmy. Considering the increase in cancer cell energy demand, the presence of functionally relevant carcinogenesis-inducing or environment-adapting mtDNA mutations in cancer seems plausible. We review 279 EC tumorspecific mtDNA single nucleotide variants from 111 individuals from different studies. Many transition mutations indicative of error-prone DNA polymerase g replication and C to U deamination events were present. We examine the spectrum of mutations and their heteroplasmy and discuss the potential biological impact of recurrent, non-synonymous, insertion, and deletion mutations. Lastly, we explore current EC treatments, exploiting cancer cell mitochondria for therapy and the prospect of using mtDNA variants as an EC biomarker.